Импульсная фото- и катодолюминесценция силикатного люминофора с европием; Известия вузов. Физика; Т. 58, № 6-2 - Степанов С. А. Сергей Александрович; Валиев Д. Т. Дамир Талгатович; Вишнякова Е. А. Екатерина Анатольевна; Мархабаева А. А. Айымкул Алихановна; Тулегенова А. Т. Аида Тулегенкызы; Сарасеко Д. В. Даниил Владимирович; Абдуллин Х. Б. Хабибулла Абдуллаевич; Лисицын В. М. Виктор Михайлович (2015, 2015)
Заглавие с экрана